Pembentukan Karakter Siswa Berbasis PAK Keluarga Dan Pergaulan Teman Sebaya di SMA Negeri Mamasa - Rihardes, Rihardes; Moimau, Aprianus Ledrik; Istiati, Istiati; Manurung, Jendri Leddoin (Jurnal Teologi dan Pendidikan Kristen, 2023)
The purpose of the study was to determine the meaningful contribution together between Christian Education (CE), family and peer association to the formation of student character. The research method conducted by the researcher is an ex post facto method, with a quantitative description system, data is obtained by distributing questionnaires. Based on the results of research calculations, the family CE tendency test (X1) of 46.6% was categorized as good, the peer association tendency test (X2) of 43.33% was categorized as good, and the tendency test of student character building (Y) 33.33% was categorized as poor. While the contribution between family CE (X₁) to character formation (Y) is 0.985, when compared with the rtable price for N = 30 at a 5% confidence level, the results obtained are calculated> rtable (0.985>0.396). While the peer association variable (X2) on character formation (Y) is 0.893, the results obtained are calculated > rtable (0.893>0.396). While the family CE variable (X1) with peer association (X2) is 0.545, the results obtained are calculated > rtable (0.545>0.361). Thus, it can be concluded that there is a meaningful and significant contribution from family CE (X₁) and peer association (X₂) to the formation of student character (Y).